DIAGNOSTIC CRITERIA FOR THE FORMATION OF GLAUCOMATOUS OPTIC NEUROPATHY AT THE VARIOUS STAGES OF THE DISEASE - A. G. Shchuko; Y. S. Pyatova; T. N. Iureva; A. S. Grishchuk (Acta Biomedica Scientifica)
Purpose: to identify the most informative diagnostic criteria for the formation of glaucomatous optic neuropathy at various stages of the pathological process. Methods: 94 people with early stages of glaucoma were examined using spectral optical tomography, chromatic methods of perimetry, electroretinography and electrophysiological examination. The following main criteria for inclusion of patients in the study were identified: elevated levels of intraocular pressure (IOP), visual acuity not less than 0.6, similar in dimensions to the value of the optic nerve, which allowed comparing the results of research in these patients populations. Thus, through careful clinical analysis of data and assessment of excavation size of the optic nerve, using certain optical coherence tomography (OCT), all patients were divided into 3 groups. To get an accurate representation of the formation features of glaucomatous neuropathy it was necessary to evaluate not only the structural changes of the retina and optic nerve, but also the changes of their functional activity in all groups. Results: The most important criterion for the structural changes of the retina in patients in the latent stage of the pathological process was the global indicator of the volume loss of ganglionic complex (GLV %). IOP decrease in this group of patients was accompanied by normalization criteria of central perimetry, PERG, which is indicating their functional transient depression on the background of elevated intraocular pressure. Decrease perimeter indices of all kinds of computer perimetry were observed in patients with more advanced stage of disease.